Masa Depan Pekerjaan dalam Organisasi Agile: (Peran SDM dalam Menavigasi Volatilitas Ekonomi) - Sujoko Winanto; Abdul Haris Muchtar (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
In the context of accelerating global economic volatility, organizations are increasingly required to adopt agile business models that enable them to remain competitive and resilient. Although business agility has been extensively discussed from structural and technological perspectives, the strategic role of Human Resources (HR) in shaping agile organizations and addressing the future of work remains insufficiently explored. This study aims to examine how HR contributes to organizational adaptability and resilience in uncertain environments by aligning human capital practices with agile frameworks. Using a mixed-methods approach, data were collected through surveys and semi-structured interviews with HR leaders and employees in industries most exposed to economic disruption, including finance, technology, and manufacturing. The findings reveal four critical dimensions of HR’s role: workforce flexibility achieved through reskilling initiatives and adaptive work arrangements; agile leadership development to enhance decision-making under uncertainty; prioritization of employee well-being and engagement as foundations of organizational resilience; and digital HR transformation leveraging analytics and artificial intelligence to strengthen efficiency and collaboration. These findings validate and extend the existing literature, demonstrating that HR is not merely a supporting or administrative function but a strategic driver of agility. The study concludes that by embedding HR strategies into organizational agility frameworks, companies can better navigate economic turbulence, enhance workforce adaptability, and secure long-term competitiveness in the global market.